Enhancing University Students’ Academic Reading Comprehension through ChatGPT-Assisted Instruction in Indonesian Higher Education - M. Iqbal Tawakkal; Sumadi; Djoko Apriono (Merwinspy Publisher, 2026)
Academic reading comprehension is an essential competency in higher education because students are required to critically understand and evaluate academic texts. However, many university students still experience difficulties in comprehending academic materials due to limited reading strategies and low engagement. This study aimed to investigate the implementation of ChatGPT-assisted instruction and examine its contribution to enhancing students’ academic reading comprehension in higher education. This study employed a mixed-methods approach with a quasi-experimental design involving 60 undergraduate students divided into an experimental group and a control group. The intervention was conducted for eight weeks. The data were collected through reading comprehension tests, classroom observations, and semi-structured interviews and analyzed using quantitative statistical analysis and thematic analysis. The findings revealed that students who participated in AI-assisted instruction achieved significantly higher improvement in reading comprehension compared to those who received conventional instruction. The statistical analysis showed significant improvement in the experimental group (p = 0.001). The qualitative findings also indicated that AI-assisted instruction increased students’ engagement, motivation, and interaction during reading activities. The study concludes that AI-assisted instruction can serve as an effective pedagogical approach to support academic literacy development in higher education.